2020
DOI: 10.1111/tpj.15047
|View full text |Cite
|
Sign up to set email alerts
|

Maize metacaspases modulate the defense response mediated by the NLR protein Rp1‐D21 likely by affecting its subcellular localization

Abstract: SUMMARYPlants usually employ resistance (R) genes to defend against the infection of pathogens, and most R genes encode intracellular nucleotide‐binding, leucine‐rich repeat (NLR) proteins. The recognition between R proteins and their cognate pathogens often triggers a rapid localized cell death at the pathogen infection sites, termed the hypersensitive response (HR). Metacaspases (MCs) belong to a cysteine protease family, structurally related to metazoan caspases. MCs play crucial roles in plant immunity. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 86 publications
(163 reference statements)
0
12
0
Order By: Relevance
“…Several studies have used the Rp1-D21 mt to identify genes or loci associated with modulation of the severity of HR (Chintamanani et al, 2010;Chaikam et al, 2011;Olukolu et al, 2014). We have verified that two homolog genes encoding enzymes of lignin biosynthesis pathway ZmHCT1806 and ZmCCoAOMT2 (Wang et al, 2015b;Wang and Balint-Kurti, 2016), two flavone synthase homologs of ZmFNSIs (Zhu et al, 2020), the nicotinate N-methyl transferase ZmNANMT (Liu et al, 2021), and the metacaspase homologs, ZmMC1 and ZmMC2 (Luan et al, 2021), can suppress Rp1-D21-mediated HR likely through physical interaction with the cellular component (CC) signaling domain of Rp1-D21 when transiently expressed in Nicotiana benthamiana. Interestingly, ZmCCoAOMT2 was also proved to confer quantitative resistance to both southern leaf blight and gray leaf spot in maize (Yang et al, 2017).…”
Section: The Autoactive Rp1-d21 Mt Is An Excellent Tool For the Identification Of Disease Resistance Genes In Maizementioning
confidence: 69%
See 1 more Smart Citation
“…Several studies have used the Rp1-D21 mt to identify genes or loci associated with modulation of the severity of HR (Chintamanani et al, 2010;Chaikam et al, 2011;Olukolu et al, 2014). We have verified that two homolog genes encoding enzymes of lignin biosynthesis pathway ZmHCT1806 and ZmCCoAOMT2 (Wang et al, 2015b;Wang and Balint-Kurti, 2016), two flavone synthase homologs of ZmFNSIs (Zhu et al, 2020), the nicotinate N-methyl transferase ZmNANMT (Liu et al, 2021), and the metacaspase homologs, ZmMC1 and ZmMC2 (Luan et al, 2021), can suppress Rp1-D21-mediated HR likely through physical interaction with the cellular component (CC) signaling domain of Rp1-D21 when transiently expressed in Nicotiana benthamiana. Interestingly, ZmCCoAOMT2 was also proved to confer quantitative resistance to both southern leaf blight and gray leaf spot in maize (Yang et al, 2017).…”
Section: The Autoactive Rp1-d21 Mt Is An Excellent Tool For the Identification Of Disease Resistance Genes In Maizementioning
confidence: 69%
“…Several Rp1-D21 regulators we identified previously interact with CC D21 and suppress CC D21 -mediated HR (Wang et al, 2015b;Wang and Balint-Kurti, 2016;Zhu et al, 2020;Liu et al, 2021;Luan et al, 2021). To investigate whether ZmUGTs can interact with CC D21 , we performed yeast two-hybrid assays.…”
Section: Zmugts Have No Interaction With CC D21mentioning
confidence: 99%
“…To our knowledge, it has not been reported previously in any species that NA N MTs can play a role in the plant defence response. Although most data were derived from the ectopic system using Agrobacterium ‐mediated transient over‐expression in N. benthamiana , we believe it can largely reflect the situation in the endogenous maize system for the reasons mentioned previously (Luan et al., 2020; Wang, Ji, et al., 2015). We hope to verify these results when maize genetic materials are available in the future.…”
Section: Discussionmentioning
confidence: 98%
“…We previously reported that both Rp1‐D21 and CC D21 are located in the nucleus and cytoplasm, and that nucleocytoplasmic trafficking plays an important role in auto‐HR induction (Wang & Balint‐Kurti, 2015). We have recently shown that two type I maize metacaspases (ZmMCs), ZmMC1 and ZmMC2, interact with CC D21 and change its subcellular localization to suppress auto‐HR (Luan et al., 2020). When ZmNA N MT was coexpressed with CC D21 in N. benthamiana , it did not cause the redistribution of CC D21 in plant cells (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation